2012
DOI: 10.1182/blood.v120.21.677.677
|View full text |Cite
|
Sign up to set email alerts
|

Phase I/II Trial of the MEK1/2 Inhibitor Trametinib (GSK1120212) in Relapsed/Refractory Myeloid Malignancies: Evidence of Activity in Patients with RAS Mutation-Positive Disease

Abstract: 677 Background: Activating mutations of NRAS and KRAS (‘RAS’) are found in 10–30% of myeloid malignancies. Evidence of constitutive activation of the RAS-RAF-MEK-ERK pathway, however, is more ubiquitous. Trametinib is a potent, selective, allosteric inhibitor of MEK1/2 that inhibits proliferation of myeloid cell lines in vitro. A Phase I/II study of single, daily, oral dosing of trametinib in myeloid malignancies is ongoing. Here we report the results from Ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Although we do not have information regarding the status of the patient’s bone marrow and the current allele burden of the NRAS-G12D mutation, his overall depth and duration of response strongly suggests that targeting the RAS-RAF-MEK-ERK may provide significant hematologic and clinical benefit to patients with aCML and perhaps other hematologic malignancies with NRAS mutations. Indeed, an ongoing Phase I/II clinical trial of trametinib has noted promising clinical activity in patients with RAS -mutated relapsed/refractory myeloid malignancies [ 9 ], and two Phase II clinical trials are underway to evaluate the safety and efficacy of trametinib treatment in combination with an AKT inhibitor for AML and multiple myeloma. When completed, the results of these studies may provide greater insight into the benefits of targeting MEK1/2 in hematologic malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…Although we do not have information regarding the status of the patient’s bone marrow and the current allele burden of the NRAS-G12D mutation, his overall depth and duration of response strongly suggests that targeting the RAS-RAF-MEK-ERK may provide significant hematologic and clinical benefit to patients with aCML and perhaps other hematologic malignancies with NRAS mutations. Indeed, an ongoing Phase I/II clinical trial of trametinib has noted promising clinical activity in patients with RAS -mutated relapsed/refractory myeloid malignancies [ 9 ], and two Phase II clinical trials are underway to evaluate the safety and efficacy of trametinib treatment in combination with an AKT inhibitor for AML and multiple myeloma. When completed, the results of these studies may provide greater insight into the benefits of targeting MEK1/2 in hematologic malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…Parallel siRNA and small molecule screens demonstrated the functional importance of the activated NRAS/Raf/MEK/ERK pathway in vitro. MEK inhibitors such as trametinib have shown activity in RAS-mutated AML; however, the overall response rate is only 28 %, indicating that a RAS mutation by itself is not sufficient to predict which patients will respond to therapy [ 14 ]. While trametinib monotherapy did not lead to CR in this patient, it did reduce peripheral blast counts and provided 6 months of disease control, allowing time to potentially coordinate a stem cell transplant.…”
Section: Case Presentationmentioning
confidence: 99%
“…[8][9][10][11][12][13] In RKO tumor xenograft models, AMG 232 had antitumor activity as monotherapy that was enhanced in combination with a MEK inhibitor. 10 Furthermore, phase 1 clinical studies have shown evidence of efficacy with MDM2 inhibitors and MEK inhibitors in AML, 14,15 suggesting that combination therapy may result in greater clinical activity. In clinical studies, increased blood levels of macrophage inhibitor cytokine-1 (MIC-1) has been used as a pharmacodynamic marker of treatment with other MDM2 inhibitors in patients with relapsed/refractory AML and in patients with other solid tumors, indicating on-target biological activity.…”
Section: Introductionmentioning
confidence: 99%